Pendampingan Masyarakat dalam Pengolahan dan Pemasaran Produk Berbahan Dasar Pisang untuk Meningkatkan Kemandirian Ekonomi Lokal - Ahmad Suyanto; Siti Nur Farida; Nur Lailatul Fitri; Vita Fitriatul Ulya (Journal of Community Engagement in Economics, 2025)
This research was conducted in Dagangan Village, Parengan District, Tuban Regency, with the aim of developing processed banana products into original banana chips and melted chocolate banana chips. Kepok bananas were chosen as the raw material based on their dense texture and distinctive flavor. The research method included material selection, peeling, slicing, frying, chocolate coating (for the melted variant), cooling, packaging, labeling, and organoleptic testing. The results showed that the original banana chips produced a crispy and savory product, while the melted chocolate variant offered a modern, innovative flavor that was more appealing to children and teenagers. The simple processing process allows the village community to produce chips with limited capital, although challenges such as high oil content and chocolate stability at room temperature remain. Airtight packaging and informative labels have been shown to maintain quality and increase product appeal in the market. Economically, the banana chip business can increase community income, create new jobs, and strengthen village independence. This study concluded that banana chips have significant potential as a superior product in Dagangan Village and can be further developed through training, technological innovation, and digital marketing strategies.